Juridical Analysis Of Application Of Forgiveness (Rechterlijk Pardon) As A Basis Of Judge Consideration In Deciding The Criminal - Sisno Pujinoto; Anis Mashdurohatun; Achmad Sulchan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
The formulation of the problem in this study are: How is the principle position Rechterlijk Pardon in the criminal system in Indonesia, how the principles are applied Rechterlijk Pardon in a criminal ruling Decision Number 241 / Pid.B / 2019 / PN.Mjl andHow the development / concept of the Rechterlijk Pardon principle in the renewal of the Indonesian criminal law that will come related to the draft criminal law on the monodualistic principle?This study uses a sociological juridical approach, with descriptive analytical research specifications. The data used in this study are secondary data obtained through library research and primary data obtained through field research which are then analyzed qualitatively using legal theory, the forgiveness agency theory, criminal justice system theory, and progressive legal theory. Based on the results of that study The position of the Rechterlijk Pardon Principle in the Criminal System in Indonesia is forgiveness is a form of forgiveness / deliverance from mistakes made. As a form of forgiveness, then with forgiveness, someone who is guilty is not sentenced or does not need to feel the punishment. Provisions such as this basically exist in conditional criminal conduct (voorwaardelijke veroordeling) regulated in Article 14a-14f of the Criminal Code. Conditional penalties are also referred to by part of the community with the term criminal trial or there is also termed as conditional punishment. Application of the Rechterlijk Pardon Principle in Criminal Verdicts Number 241 / Pid.B / 2019 / PN.Mjl it is applied later to act as the final safety valve in the criminal justice system if a case is not filtered at the prosecution and preliminary hearing judge stage. Development / Concept of the Rechterlijk Pardon Principle in the Future Renewal of Indonesian Criminal Laws Associated with the Draft Criminal Laws on the Monodualistic Principle are Forgiveness institution, is an important element to answer problems that cannot be accommodated with only 3 (three) types of decisions (free, loose, criminal funds).Keywords : Institutions; Forgiveness; Rechterlijk Pardon; Considerations; Judges; Decisions.